Anti-transferrin receptor antibody and antibody-drug conjugates cross the blood-brain barrier. - Friden, P M (1991)
Delivery of nonlipophilic drugs to the brain is hindered by the tightly apposed capillary endothelial cells that make up the blood-brain barrier. We have examined the ability of a monoclonal antibody (OX-26), which recognizes the rat transferrin receptor, to function as a carrier for the delivery of drugs across the blood-brain barrier. This antibody, which was previously shown to bind preferentially to capillary endothelial cells in the brain after intravenous administration (Jefferies, W. A., Brandon, M. R., Hunt, S. V., Williams, A. F., Gatter, K. C. & Mason, D. Y. (1984) Nature (London) 312, 162-163), labels the entire cerebrovascular bed in a dose-dependent manner. The initially uniform labeling of brain capillaries becomes extremely punctate approximately 4 hr after injection, suggesting a time-dependent sequestering of the antibody. Capillary-depletion experiments, in which the brain is separated into capillary and parenchymal fractions, show a time-dependent migration of radiolabeled antibody from the capillaries into the brain parenchyma, which is consistent with the transcytosis of compounds across the blood-brain barrier. Antibody-methotrexate conjugates were tested in vivo to assess the carrier ability of this antibody. Immunohistochemical staining for either component of an OX-26-methotrexate conjugate revealed patterns of cerebrovascular labeling identical to those observed with the unaltered antibody. Accumulation of radiolabeled methotrexate in the brain parenchyma is greatly enhanced when the drug is conjugated to OX-26.